Analysis of Chlorophyll and Vegetative Growth of Green Eggplant (Solanum Malongena L.) Based on NPK and Bokashi Fertilizer Application - Nabila, Hesti; Raksun, Ahmad; Japa, Lalu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The availability of vital macronutrients from NPK fertilizer and the enhancement of soil fertility with bokashi organic fertilizer have a significant impact on the vegetative growth of green eggplant (Solanum melongena L.). This study aims to determine the effect of NPK, bokashi, and a combination of both on the chlorophyll content and vegetative growth of green eggplant. NPK fertilizer dosage (0 g, 1 g, 1.5 g, and 2 g) and bokashi fertilizer dosage (0 g, 100 g, 200 g, 300 g, and 400 g) were the two components in this study, which employed a completely randomized design (CRD) with three replicates. Plant height, leaf count, leaf area, fresh weight, dry weight, and chlorophyll content were among the metrics measured. ANOVA at the 5% level and DMRT were used to analyze the data. The findings demonstrated that the chlorophyll content and other vegetative growth indices were significantly impacted by NPK fertilizer. Chlorophyll content was not considerably impacted by the bokashi fertilizer application, however all vegetative growth indices were significantly impacted. With the exception of leaf area, the combination of NPK and bokashi fertilizers did not substantially affect most measures. The combination of 400 g bokashi and 2 g NPK yielded the highest vegetative growth indices and was the best treatment. Meanwhile, the combination of NPK 2 g and bokashi 300 g produced the maximum chlorophyll content. Through the use of integrated organic and inorganic fertilization, this study demonstrates how adding bokashi to NPK fertilizer can boost plant growth and nutrient use efficiency, helping to create sustainable farming methods.